Food aid and informal insurance - Stefan Dercon; Pramila Krishnan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Households in developing countries use a variety of informal mechanisms to cope with risk, including mutual support and risk-sharing. These mechanisms cannot avoid that they remain vulnerable to shocks. Public programs in the form of food aid distribution and food-for-work programs are meant to protect vulnerable households from consumption and nutrition downturns by providing a safety net. In this paper we look into the extent to which food aid helps to smooth consumption by reducing the impact of negative shocks, taking into account informal risk-sharing arrangements. Using panel data from Ethiopia, we find that despite relatively poor targeting of the food aid, the programs contribute to better consumption outcomes, largely via intra-village risk sharing.
Keywords: D91; I38; O17; 330; risk-sharing; informal insurance; safety nets; food aid; Nahrungsmittelhilfe; Äthiopien; Soziales Netzwerk